Impact of Instructional Supervision Strategies on Teacher Performance in Hinabangan Samar District 1 - Castillo, Mitchel A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The effectiveness of instructional supervision strategies on teacher performance is a critical area of educational research. This study aimed to determine the effectiveness of different instructional supervision strategies employed by school heads and their impact on the instructional performance of teachers in the Hinabangan Samar District I. This study utilized the descriptive-correlational research design using the researcher-developed survey questionnaire administered to 81 public school teacher-respondents who were randomly sampled. The high effectiveness of school heads' instructional supervision practices in the Hinabangan Samar District I as evidenced by a composite mean of 4.82 highlights the positive influence of strong leadership and supportive practices. The very high positive correlation observed in the Hinabangan Samar District I reinforce the importance of robust supervision systems in educational settings. School heads should prioritize regular classroom observations, provide constructive feedback, and offer professional development opportunities. Additionally, fostering a collaborative culture among teachers can further enhance the effectiveness of instructional supervision.